A novel microwave assisted reverse micelle fabrication route for Th (IV)‐MOFs as highly efficient adsorbent nanostructures with controllable structural properties to CO and CH4 adsorption: Design, and a systematic study. (12th February 2019) - Sargazi, Ghasem; Afzali, Daryoush; Mostafavi, Ali
Abstract : Reducing gas contaminants by affordable and effective adsorbents is a major challenge in the 21 st century. In the present study, thorium metal organic framework (Th‐MOF) nanostructures are introduced as highly efficient adsorbents. These compounds were manufactured via a novel route resulting from the development of microwave assisted reverse micelle (MARM) and ultrasound assisted reverse micelle (UARM) methods. The products were characterized utilizing XRD, SEM, TGA/DSC, BET, and FT‐IR analyses. Based on the results, the samples synthesized by MARM had uniform size distribution, high thermal stability, and significant surface area. Calculations using DFT/B3LYP indicated that the compounds have a tendency to the polymeric form, which could theoretically confirm the formation of Th‐MOF. Results of analysis of variance (ANOVA) showed that synthesis parameters played a critical role in the manufacturing of products with distinctive properties. Response surface methodology (RSM) predicted the possibility of creating Th‐MOF adsorbents with the surface area of 2579 m 2 /g, which was a considerable value in comparison with the properties of other adsorbents. Adsorption studies showed that, in the optimum conditions, the Th‐MOF products had high adsorption capacity for CO and CH4 . It is believed that the synthesis protocol developed in the present study and the systematic studies conducted on the samples which lead to products with ideal adsorption properties. Abstract : A simple schematic of the synthesis process of the Th‐MOF samples for CO and CH4 adsorption.